Identification of microbial contaminants in sinus rinse squeeze bottles used by allergic rhinitis patients - Shaun A. Nguyen (KeAi Communications Co., Ltd., 2019)
Objective: To identify whether irrigation devices become contaminated when used by patients with allergic rhinitis (AR). Methods: Ten AR patients with no clinical or endoscopic evidence of active sinonasal infection were given a sinus rinse system and instructed on its proper use, cleaning, and storage. Two squeeze bottles (bottle A and bottle B) were given to each patient for twice-a-day rinsing. Bottle A was used in the morning and analyzed after four weeks. Bottle B was used in the evening and analyzed after 8 weeks of use. Microbial contaminants were cultured from the nose pieces and the inner surface of the bottles obtained from patients. Results: Seventeen sinus rinse devices (17/20) from all individuals in this study grew bacteria commonly in the nozzles. Twenty-four bacterial isolates consisting of 14 different species were cultured and identified with most common organisms being bacilli and staphylococcus. In addition, no correlation was apparent between the length of bottle use and the degree of contamination (r = 0.13, p = 0.76). During the study period, no patient developed acute sinus infections. Conclusion: Microbial contamination of the sinus rinse system occurs commonly, even in uninfected AR patients; however no evidence exists linking this to clinically relevant sinus infections. Trial Registration: clinicaltrials.gov Identifier: NCT01030146. Keywords: Allergic rhinitis, Microbial contaminants, Sinus irrigation, Sinus rinse, Squeeze bottles